56‐3: New Ultra Low‐Power High Brightness Microdisplays Enabling Broad Applications. Issue 1 (28th June 2022) - Wartenberg, Philipp; Fritscher, Andreas; Brenner, Stephan; Richter, Bernd; Lenk, Simone; Rolle, Martin; Baumgarten, Judith; Fehse, Karsten; Schmidt, Christian; Vogel, Uwe
Abstract : This paper reports on the latest development on ultra low‐power microdisplays. Initially this architecture has been presented in a monochrome version in [4]. Due to the demand of extended applications beyond pure information displays towards situation aware notifications a new colored version has been developed with the main achievement of cutting down the pixel size by more than a factor of two to enable color sub‐pixels. Furthermore special attention was paid on very high brightness to also enable implementation in situation‐aware augmented reality optics.